Colloidal processing of fully stabilized zirconia laminates comprising graphene oxide-enriched layers. Issue 7 (June 2016) - Rincón, Acacio; Moreno, Rodrigo; Gutiérrez-González, Carlos Fidel; Sainz, Raquel; Salvador, María Dolores; Borrell, Amparo
Abstract: Multilayer materials have demonstrated to provide an efficient mechanism for toughening by deflection of a propagating crack by weak interlayers. Therefore, the aim of this work is to study the colloidal processing of 8 mol% yttria stabilized zirconia (8YSZ) based laminates by intercalating thin layers of graphene enriched with 8YSZ, and to evaluate the advantages of such multilayered structure in the propagation of cracks induced by indentation. Green tapes of 8YSZ and graphene-oxide with YSZ were obtained by aqueous tape casting and sintered in one-step by spark plasma sintering at 1400 °C. Microindentation results showed that the indentation cracks propagate within the horizontal direction within the ceramic layer, but in the cross-sectional direction the presence of the GO-rich layers stops the cracks without deflection or bifurcation. The hardness and elastic modulus values were higher than 17.6 GPa and 230 GPa, respectively, and similar for all layers.